2007
DOI: 10.2478/v10053-008-0012-5
|View full text |Cite
|
Sign up to set email alerts
|

Common-onset masking simulated with a distributed-code model

Abstract: A distributed-coding model incorporating lateral inhibition in a simulated nerve network has been successful in accounting for many properties of backward masking (Bridgeman, 1971, 1978), linking modeling with neurophysiology and psychophysics. Metacontrast is a variety of backward masking that is of particular interest in uncovering properties of visual coding because target and mask do not overlap in time or space, and it is the first stimulus that is reduced in visibility, not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Strong evidence in favor of Bridgeman's (2007) model is that it produces U-shaped masking functions like those seen in recovery from OSM. The explanation for this pattern of masking is based on the timing of mask offset and target signals and their interaction within the model.…”
Section: Theories Of Osmmentioning
confidence: 99%
See 2 more Smart Citations
“…Strong evidence in favor of Bridgeman's (2007) model is that it produces U-shaped masking functions like those seen in recovery from OSM. The explanation for this pattern of masking is based on the timing of mask offset and target signals and their interaction within the model.…”
Section: Theories Of Osmmentioning
confidence: 99%
“…While initial attempts to model OSM without recourse to reentrant processing fell short of accurately operationalizing important concepts like attention (Francis & Hermens, 2002), more recent developments have provided excellent predictive value in a way that is theoretically sound (Põder, 2013). Bridgeman's (2007) model does one of the best jobs in approximating the behavioral data of OSM, but this is a model of recurrent lateral inhibition, rather than feedback, between different regions. However, the physiological reality is that the brain has substantial architecture for reentrant processing, and much evidence points to this being involved in conscious perception (Lamme & Roelfsema, 2000).…”
Section: Theories Of Osmmentioning
confidence: 99%
See 1 more Smart Citation
“…Pattern as well as metacontrast masking seems to involve complex spatial interactions that may be best explained with spatial perceptual grouping. Still, Bruce Bridgeman (this volume) and Hermens and Ernst (this volume) showed that simple neural network models can simulate many masking effects, including some of these spatial effects. Other discussions emphasized that the modeling work needs to account for task-set influences on processing speed and phenomenally perceived temporal characteristics (e.g., temporal order of stimuli, perceived duration of ISIs, or perceived stimulus duration) under masking conditions (Ansorge et al, this volume).…”
Section: The Workhop Goalsmentioning
confidence: 99%
“…After reaching a minimum of visibility (maximum of masking) at some intermediate SOA, target visibility increases. Whether Type A or Type B masking is produced depends on the target, mask, experimental task, and conditions of the experiment, as is discussed in other papers in this issue (Breitmeyer this volume, Bridgeman this volume, Herzog, this volume). …”
mentioning
confidence: 96%